Analysis of Low Voltage Cable Insulation Resistance Test in PT. PLN (Persero) UPP Sumbagut 1 Building - Khairul Fahredha; Muhammad Erpandi Dalimunthe; Dicky Lesmana (INFOKUM, 2025)
Insulation resistance testing is an important part of electrical installation system maintenance to ensure system safety and reliability. This study aims to analyze the condition of low-voltage cable insulation in the PT. PLN (Persero) UPP Sumbagut 1 building through insulation resistance testing using a megger. Measurements were conducted at several distribution panel points by comparing the results with the 2011 PUIL standard. The test results showed a decrease in insulation quality at several points, especially in the generator panel area, which has the potential to cause disruption to the power distribution system. The decrease in insulation resistance can be influenced by various factors such as cable age, environmental humidity, and installation conditions. This study provides recommendations for preventive measures in the form of cable replacement at critical points and the implementation of periodic testing to maintain the performance of the electrical system. In addition, evaluation of installation design and environmental control is also needed to increase cable service life and overall system efficiency.